Apocalypse in Vienna: Biblical Visions about the Ottoman Siege of the Danube Capital (1529) - Gozalbo Nadal, Antonio (Eikón / Imago, 2020)
This article analyze several artistic representations in which outstanding biblical passages were equated with the Turkish siege of Vienna in 1529.The emergence of the Ottomans in the Mediterranean and Eastern Europe caused a growing interest in knowing and defining the otther Ottoman. The evidence of his military power was going to propitiate the appearance of images in which the Turk was defined as an infernal and merciless enemy, whose actions represented the fulfillment of fear some apocalyptic prophecies. These compositions sought to create affinities and ensure the support of the Christianity to Emperor Charles the Fifth, the only legitimized and capable according to this effective messages to unify Europe to overpower the terrible infidel enemy.